3D-built VR arctic environment with mindfulness track enhances awe through restorativeness - Romano, Luciano; Clemente, Davide; Theodorou, Annalisa; Russo, Claudia; Barbato, Simone; Panno, Angelo (Journal of Environmental Psychology, 2024)
Studies highlighted the effectiveness of exposure to virtual natural environments in enhancing awe. Nevertheless, the mechanisms through which this occurs and the methodologies that can help strengthen this effect are less investigated. We propose that a VR arctic environment with a mindfulness track – compared to a VR arctic environment without a mindfulness track and a VR urban environment with a mindfulness track – should be more effective in enhancing awe through restorativeness. Participants (86 students) were randomly assigned to three conditions in a between-subject design: 1) 3D-built VR arctic environment with mindfulness track, 2) 3Dbuilt VR urban environment with a mindfulness track, and 3) 3D-built VR arctic environment without a mindfulness track. Results of mediation analysis with multicategorical predictors, as expected, show the superior effectiveness of the exposure to a VR arctic environment with mindfulness track (vs. the same environment without mindfulness track and an urban environment with mindfulness track). Practical implications and future research directions are discussed.